2007
DOI: 10.1128/aem.00072-07
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Production by Pseudomonas stutzeri under Aerobic and Anaerobic Conditions

Abstract: The siderophore production of the facultative anaerobe Pseudomonas stutzeri, strain CCUG 36651, grown under both aerobic and anaerobic conditions, was investigated by liquid chromatography and mass spectrometry. The bacterial strain has been isolated at a 626-m depth at the Äspö Hard Rock Laboratory, where experiments concerning the geological disposal of nuclear waste are performed. In bacterial culture extracts, the iron in the siderophore complexes was replaced by gallium to facilitate siderophore identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Under aerobic condition, Pseudomonas stutzeri CCUG 36651 was reported to produce four ferrioxamine siderophores. In contrast, none of these ferrioxamines siderophores were found under anaerobic conditions (Essen et al 2007). Siderophore first binds with iron (Fe +3 ) tightly and then the siderophore-iron complex moves into the cell through the cell membrane using the specific siderophore receptors.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Under aerobic condition, Pseudomonas stutzeri CCUG 36651 was reported to produce four ferrioxamine siderophores. In contrast, none of these ferrioxamines siderophores were found under anaerobic conditions (Essen et al 2007). Siderophore first binds with iron (Fe +3 ) tightly and then the siderophore-iron complex moves into the cell through the cell membrane using the specific siderophore receptors.…”
Section: Introductionmentioning
confidence: 96%
“…Generally, most of the aerobic and facultative anaerobic bacteria were found to produce siderophore under iron stress condition (Neilands 1995). It has been reported that a facultative aerobic bacterium Pseudomonas stutzeri CCUG 36651 can produce siderophores in both aerobic and anaerobic conditions, but the siderophore produced in aerobic condition varies from siderophores produced in anaerobic condition (Essen et al 2007). Under aerobic condition, Pseudomonas stutzeri CCUG 36651 was reported to produce four ferrioxamine siderophores.…”
Section: Introductionmentioning
confidence: 98%
“…could produce high concentrations (9 nM) of ferrioxamine B and (13 nM) of ferrioxamine G, respectively. However, Essén et al (2007) showed that P. stutzeri could produce ferrioxamine E as the main siderophore together with ferrioxamine G. In the present study, the isolated N. tenerifensis and N. farcinica produced all the ferrioxamine types except ferrioxamines E. Moreover, both isolates were characterized by high concentrations of ferrioxamine D (17 nM) for N. tenerifensis and (15 nM) for N. farcinica.…”
Section: Pseudomonas)mentioning
confidence: 73%
“…Furthermore, Kobayakawa and Kodani detected by high-performance liquid chromatography (HPLC) the production of desferrioxamines in 78% of their Streptomyces collection (61). Desferrioxamines are also produced by other actinomycetes and some Gram-negative bacteria (62,63).…”
Section: Discussionmentioning
confidence: 99%